An Objective Structured Clinical Examination (OSCE): strengthening confidence and clinical skills / Nor Elyzatul Akma Hamdan and Associate Prof. Dr. Mahmathi Karuppannan - Hamdan, Nor Elyzatul Akma; Karuppannan, Mahmathi (Faculty of Pharmacy, 2023)
An Objective Structured Clinical Examination (OSCE) for third-year and fourth-year pharmacy students was held on July 5th and 11th, 2023, respectively. OSCE is an approach to assess students' clinical competency in a planned and structured manner. OSCE emphasizes the communication and clinical intervention skills for pharmacists in training. It is essentially an organizational framework consisting of several stations, in which students will be rotated, and are assessed on specific tasks.